Gênero, performance, precariedade: um estudo sobre o pensamento de Judith Butler - Rodrigues, Natália Teixeira (2020)
This work presents the theoretical development of the philosopher Judith Butler more specifically regarding three concepts: gender, performance and precarity. For this purpose, the text is divided in three main chapters. Firstly, we expose the theoretical concept of the three waves that characterize the feminist movement, because we understand that the theoretical genesis of the gender concept was founded in this historical moment, specifically in the second wave with the Simone Beauvoir’s book The Second Sex. Secondly, we show the critical analysis of Judith Butler to the gender concept, from what she calls genealogy of gender ontology. This analysis was founded in a identity sex/gender system that results in some problems to be thinking philosophically. Among them, the formation of binary sexuality that exclude bodies with gender conformity. Alternatively, the author propose a critic to the gender identity from the theory of gender performativity. This theory has the basis on the Butler’s psychoanalysis studies, fundamentally the taboo of homosexuality that constitutes the psychic formation of the subject, even before, the taboo of incest. Finally, in the last chapter, we recognize that a political of identity is not capable to provide a wide concept of a common living. As an ethic-political result, Butler propose a critic of non-recognized dependency as the origin of a new politics of bodies, in which, the comprehension of precariousness is immanent to each and every body. Therefore, we present in the last chapter the relation between the precarity and performativity with the purpose to suggest the formation of a new political alliance capable to modify a new way of life based on the exclusion of bodies without gender conformity and precarious.